Pengaruh Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening - Ramadhan, Muh. Firmansyah; Idris, Rabihatun; Abdullah, Salma (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to examine the effect of leadership, compensation, and work motivation on employee performance both directly and indirectly with work motivation as an intervening variable in 150 employees of PT Bank Rakyat Indonesia (Persero), Tbk Panakkukang Branch Makassar. Data collection using primary data obtained from questionnaires using total sampling technique. The results of hypothesis testing were carried out with the help of Smart-PLS version 3.0 so that evidence was obtained that directly showed that leadership had a positive and significant effect, compensation had a positive and insignificant effect, and work motivation had a positive and significant effect on employee performance, leadership and compensation had a positive and significant effect on work motivation. In testing the indirect effect, it is found that leadership and compensation have a positive and significant effect on employee performance with work motivation as an intervening variable.